2003
DOI: 10.1210/jc.2002-021582
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Aminopeptidase A Expression during Angiotensin II-Induced Choriocarcinoma Cell Proliferation through AT1Receptor Involving Protein Kinase C- and Mitogen-Activated Protein Kinase-Dependent Signaling Pathway

Abstract: Angiotensin II (Ang II) is a bioactive peptide of the renin-angiotensin system, exerting its actions not only as a vasoconstrictor, but also as a growth promoter. In human placenta, type 1 Ang II receptors (AT(1)R) are predominantly expressed in trophoblasts, and we previously reported that aminopeptidase A (APA), a cell surface peptidase that converts Ang II to Ang III, is also expressed in both normal and neoplastic trophoblasts. However, the roles of Ang II and APA in trophoblast function remain to be clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…As a negative control, the primary antibody was replaced with normal rabbit IgG or mouse IgG at an appropriate dilution. As positive immunohistochemical controls, marked immunoreactivity of AT 1 R and VEGF in placental trophoblastic tissues was confirmed as reported previously (Shiraishi et al, 1996;Ino et al, 2003). The immunostaining intensity for AT 1 R and VEGF was scored semiquantitatively based on the percent positivity of stained cells on a three-tiered scale as follows: À, negative (no positive cells); ĂŸ , focally or weakly positive (o50% positive cells); ĂŸ ĂŸ , diffusely or strongly positive (450% positive cells).…”
Section: Immunohistochemistrysupporting
confidence: 67%
See 1 more Smart Citation
“…As a negative control, the primary antibody was replaced with normal rabbit IgG or mouse IgG at an appropriate dilution. As positive immunohistochemical controls, marked immunoreactivity of AT 1 R and VEGF in placental trophoblastic tissues was confirmed as reported previously (Shiraishi et al, 1996;Ino et al, 2003). The immunostaining intensity for AT 1 R and VEGF was scored semiquantitatively based on the percent positivity of stained cells on a three-tiered scale as follows: À, negative (no positive cells); ĂŸ , focally or weakly positive (o50% positive cells); ĂŸ ĂŸ , diffusely or strongly positive (450% positive cells).…”
Section: Immunohistochemistrysupporting
confidence: 67%
“…It has been reported that AT 1 R is involved in the proliferation of various cancers in vitro and in vivo (Fujimoto et al, 2001;Rivera et al, 2001;Muscella et al, 2002;Ino et al, 2003;Uemura et al, 2003). However, our immunohistochemical study showed that the AT 1 R expression score did not significantly correlate with the positivity of the cellular proliferation marker PCNA in ovarian cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessing the relationship between RAS and tumor development have shown that AT1R expression is higher in some tumor types compared to normal tissue (22,23). Other studies have shown that the expression of AT1R is upregulated in several tumor types, including laryngeal, prostate, ovarian, keratoacanthoma, glioma, squamous cell carcinoma, cervical, bladder, choriocarcinoma, pancreatic, endometrial, gastric, and others (5)(6)(7)14,15,(24)(25)(26)(27)(28). In addition, Ang II has been shown to be an important factor in tumor growth and angiogenesis through the activation of AT1R (6,29).…”
Section: Discussionmentioning
confidence: 99%
“…After combining with AT1R, Ang II can interact with several genes (9)(10)(11)(12) that promote the division and proliferation of tumor cells and inhibit cell differentiation (10,(13)(14)(15). In addition, it has been shown that local Ang II can promote the proliferation of tumor cells (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The polyclonal antirabbit AT1 receptor antibody (306, catalogue SC579) is specific for AT1 and is mouse, rat, and human reactive; it does not show cross-reactivity with AT2 (Lu et al, 1998;Ino et al, 2003Ino et al, , 2006, and AT-2 (Goat polyclonal IgG Santa Cruz Biotechnology Inc.) was 1 : 300 in BSA 1% in PBS.…”
Section: Immunohistochemistry For At1 and At2 Receptorsmentioning
confidence: 99%